2013
DOI: 10.1021/la402885k
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Well-Defined Dendrimer Encapsulated Ruthenium Nanoparticles and Their Evaluation in the Reduction of 4-Nitrophenol According to the Langmuir–Hinshelwood Approach

Abstract: This study discusses the preparation of various sized dendrimer encapsulated ruthenium nanoparticles (RuDEN) with the use of the generation 4 (G4), generation 5 (G5), and generation 6 (G6) hydroxyl-terminated poly(amidoamine) (PAMAM-OH) dendrimers as templating agents. The size of the nanoparticles ranges from 1.1 to 2.2 nm. These catalysts were fully characterized using UV/vis spectrophotometry, infrared (IR) spectroscopy, and transmission electron microscopy (TEM). The RuDEN catalysts were evaluated in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
140
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 57 publications
10
140
3
Order By: Relevance
“…The zeroorder kinetics of 4-NPh reduction was also reported for catalytic process performed on Fe@Au nanoparticles supported on graphene oxide (with k = 8.21 × 10 −6 mol dm −3 min −1 ) [2] and on Au nanoparticles grown on calcium alginate beads (k in the range 1.4-2 × 10 −6 mol dm −3 min −1 ) [20]. Since these results are in contradiction with other literature data indicating the first-order kinetics [19,31,[33][34][35][36][37][38], we performed the Fig. 3b).…”
Section: Dependence Of the Reaction Kinetics On Concentration Of 4-nphcontrasting
confidence: 58%
See 1 more Smart Citation
“…The zeroorder kinetics of 4-NPh reduction was also reported for catalytic process performed on Fe@Au nanoparticles supported on graphene oxide (with k = 8.21 × 10 −6 mol dm −3 min −1 ) [2] and on Au nanoparticles grown on calcium alginate beads (k in the range 1.4-2 × 10 −6 mol dm −3 min −1 ) [20]. Since these results are in contradiction with other literature data indicating the first-order kinetics [19,31,[33][34][35][36][37][38], we performed the Fig. 3b).…”
Section: Dependence Of the Reaction Kinetics On Concentration Of 4-nphcontrasting
confidence: 58%
“…The catalytic reduction of 4-NPh on Au nanoparticles in the concentration range up to 2.4× 10 −4 M is usually reported in the literature as the pseudo-first-order reaction with respect to 4-NPh, at excessive concentration of NaBH 4 [19,31,[33][34][35][36][37][38]. If so, the experimental data should follow a linear dependence of ln(c/c o ) on time.…”
Section: Resultsmentioning
confidence: 97%
“…The Freundlich exponents n and m which describe the heterogeneity of the catalyst are expected to be unity for a perfectly homogenous surface. However from the values of n and m obtained in our fitting (ca 0.8-1.0), it can be concluded that there is some surface heterogeneities of our catalysts, an observation reported for ruthenium dendrimerencapsulated nanoparticles [43] as well as for gold nanoparticles [44].…”
Section: Kinetic Analysissupporting
confidence: 48%
“…The analysis of the kinetic data was performed in terms of the Langmuir-Hinshelwood model [60,61], in which both reactants must be adsorbed on the surface of the nanoparticles. Similar approach has been used in many reactions [54,62,63]. A schematic representation of this model is displayed in Fig.…”
Section: Kinetic Measurementsmentioning
confidence: 99%